Sistemas De Información: Competencias Profesionales 2020 - Marisa Cecilia Tumino; Juan Manuel Bournissen; Karen Barrio (European Scientific Journal, ESJ, 2016)
Several authors warn about the necessity to adapt the university training to the professional needs demanded by society and to consider professional competencies when designing new academic programs. However, a great number of academic programs offered by European universities do not fulfill this requisite, maintaining an important discrepancy between the graduate profile and the professional profile required by society. There have been several experiences in the academic and professional realms to facilitate the integration of both profiles. The aim of the present work was to define which are the competencies of the computer science professionals, that could fulfill the expectations of the organizations requiring their professional services. In order to determine the professional competencies of the computer science professional adapted to the historical context, the competencies emerging from current professional profiles were defined after validation from the groups having real concern in this definition. A search of the professional competencies present in computer science academic programs of renowned educational institutions was conducted, compiling a list of the ones most representative of the professional performance expected in this field. These competencies were analyzed in light of the academic programs aims and then were subjected to examination by employers, faculty, students and graduated professionals. With that information, the professional competencies were defined. To analyze the results, methodology used by Maldonado Rojas (2007: 235-237) was adapted, using frequencies present for each value of a scale codified in interpretation categories. Competencies present in the final proposal were the ones belonging to the interpretative categories equal or higher than the “Satisfactory” level. The study describes the percentage of rating individuals adhering to each option of the list. From the point of view of the research design adopted, it is estimated that the list compiled during the process is appropriate for the professional profile of the computer science professional for the year 2020, since 97,6% of competencies proposed were situated in the interpretative levels of Satisfactory and Optimum. With the 80 professional competencies proposed, it is expected to contribute with the curricula design of the computer science academic programs in Latin American, or to the ones equivalent in other countries.